Impact of Ramadan Fasting on Metabolic Syndrome Criteria: Among Treated Hypertensive and Diabetic Females of Halabja - Farag, Halgord Ali (Kurdistan Journal of Applied Research, 2022)
Background and aimThe effect of Ramadan fasting (RF) among Metabolic Syndrome (MetS) patients is still argumentative. However, the majority of evidences demonstrated a beneficial effect on nearly most of metabolic criteria reduce the risk of MetS. Hypoglycemia is a significant consequence of diabetes that has been linked to an elevated the risk of cardiovascular disease (CVD) and hypertensions. However, conflicted results have been reported. Therefore, the aim of this study was to evaluate the impact of RF on Metabolic criteria among treated hypertensive and diabetic patients. MethodThis prospective observational study was carried out in a group of 73 female patients with MetS aged (20-45) years were evaluated week before and after Ramadan month having hypertension and diabetics of more than 2 years. All attending to Halabja Hospital and were treated with one daily medication based on doctor prescription. The sample random technic was used to calculate sample size and the computed sample size. The eligibility criteria for female patients having diabetic and hypertension were based on the International Diabetic Federation (IDF) definition criteria. A fasting blood sample was obtained, blood pressure was measured and BMI was calculated, fasting blood sugar, lipid profile were analyzed on all blood sample. Result There was a significant weight reduction and WC decreased. This result has been reflected on BMI as well ( p ? 0.0001). The systolic and diastolic blood pressure showed significant changes during the month of fasting. Overall, Ramadan fasting was found to decrease fasting glucose level. With regards to changes in lipid profile, fasting Ramadan was found to significant decrease in TC, and TG level. There was no significant change in serum LDL-C after Ramadan compared to baseline, however, we found a decrease in serum HDL-C levels but this change were not paralleled by any significant changes.ConclusionsThis study shows a significant improvement in cardiovascular risk factors such as lipids profile, systolic blood pressure, weight, BMI and waist circumference in subjects with a previous history of hypertensions and hyperglycemia.